2017
DOI: 10.3389/fmicb.2017.02407
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Antimicrobial Interaction between Honey and Phage against Escherichia coli Biofilms

Abstract: Chronic wounds afford a hostile environment of damaged tissues that allow bacterial proliferation and further wound colonization. Escherichia coli is among the most common colonizers of infected wounds and it is a prolific biofilm former. Living in biofilm communities, cells are protected, become more difficult to control and eradicate, and less susceptible to antibiotic therapy. This work presents insights into the proceedings triggering E. coli biofilm control with phage, honey, and their combination, achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 105 publications
(117 reference statements)
5
62
0
Order By: Relevance
“…For scanning electron microscopy (SEM) visualization, biofilms were formed on polystyrene coupons placed on 12‐well plates . Biofilm formation for both A. baumannii strains was performed as described above, adding 500 μL of bacterial suspensions (OD 600nm of 0.02) plus 500 μL of the EO (0.5× MIC), and without the EO (500 μL of LB broth) as a growth control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For scanning electron microscopy (SEM) visualization, biofilms were formed on polystyrene coupons placed on 12‐well plates . Biofilm formation for both A. baumannii strains was performed as described above, adding 500 μL of bacterial suspensions (OD 600nm of 0.02) plus 500 μL of the EO (0.5× MIC), and without the EO (500 μL of LB broth) as a growth control.…”
Section: Methodsmentioning
confidence: 99%
“…For scanning electron microscopy (SEM) visualization, biofilms were formed on polystyrene coupons placed on 12-well plates. 27 Biofilm formation for both A. baumannii strains was performed as The samples were then allowed to dry overnight in a desiccator.…”
Section: Scanning Electron Microscopy Analysis Of Biofilmsmentioning
confidence: 99%
“…The majority of these studies are based on phage-antibiotic synergism and the elimination of biofilms (Chaudhry et al, 2017;Nouraldin et al, 2016) or bacteria such as Acinetobacter baumannii (Jansen et al, 2018), Money, 2017), Pseudomonas aeruginosa (Lin et al, 2018;Uchiyama et al, 2018), S. aureus (Jo, Kim, Ding, & Ahn, 2016). There are also studies examining the interaction of phages with different agents such as honey (Oliveira et al, 2017) or disinfectants (Agún et al, 2018). In these studies, promising results were obtained when phages were used with different concentrations of agents showing antimicrobial activity.…”
Section: S Aureusmentioning
confidence: 99%
“…Pathogenic bacterial biofilms are associated with both acute and chronic infectious sites and provide protection to the bacteria from antimicrobial agents; since the drugs cannot penetrate this structural barrier (Costerton et al, 2003; Deshpande Kaistha and Kaistha, 2017). Therefore, pathogenic bacteria that form biofilms develop antibiotic resistance and are often found to be very difficult to be eliminated by the conventional antibiotics (Nouraldin et al, 2016; Oliveira et al, 2017; Fang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Bacteriophages when delivered at the infection site can replicate to produce a large number of active progeny, which in turn produce elution factors and degrading enzymes that target the polysaccharide components of the host bacteria, leading to bacterial lysis (Ghannad and Mohammadi, 2012; Vieira et al, 2012; Nouraldin et al, 2016). Though many studies have shown bacteriophage mediated mechanism of biofilm degradation, very few studies have used biofilms formed by clinical isolates (Pires et al, 2011; Danis-Wlodarczyk et al, 2015; Deshpande Kaistha and Kaistha, 2017; Oliveira et al, 2017; Ribeiro et al, 2018). Hence, there is an urgent need to identify bacteriophages that can act on the biofilms formed by bacteria isolated from wounds.…”
Section: Introductionmentioning
confidence: 99%